Morphometric properties of river basins as indicators of relative tectonic activity – Problems of data handling and interpretation - Różycka, Milena; Migoń, Piotr (Geomorphology (Amsterdam, Netherlands), 2021)
Morphometric properties of drainage basins, expressed as indices related to their shapes, altitude variability, river networks and stream profiles, are frequently used as proxy information concerning the relative intensity of uplift. Research procedures lead towards division of an area into classes of relative tectonic activity (various rates of surface uplift) and are typically based on compound indices that jointly consider various individual parameters. Given that index approaches are quantitative in nature and comprise large sets of data, their statistical treatment should become an inherent component of the workflow, whereby the results of the statistical analyses should guide the conclusions. However, various data handling issues seem to be seldom addressed or are given inadequate attention. They include selection of variables, correlation analysis, principles of classification in terms of relative tectonic activity, validity of classifications, and criteria for using specific statistical procedures. In this paper we demonstrate the need for rigorous statistical data analysis in a morphometric study, focused on an intraplate mountainous terrain in Central Europe (Orlickie-Bystrzyckie Mountains Block), subject to low or moderate uplift. We analysed 56 drainage basins within the footwall blocks of several prominent fault-generated escarpments. Following literature guidance, the hypsometric and shape characteristics of the drainage basins were considered, whereas clustering and pure-rank based approaches were tested to distinguish classes of relative tectonic activity. The results were compared with indicators of tectonic activity calculated for the escarpments themselves and using DEM-derived terrain attributes indicating enhanced erosion. In addition, we used statistical tests to identify possible lithological influence on the variability of morphometric parameters, which in this study was found to be of secondary importance. Statistical considerations neither allowed for unequivocal classification of drainage basins in terms of relative tectonic activity, nor did they reveal a clear spatial distribution pattern of drainage basins with different morphometric characteristics, typically considered to reflect tectonic forcing. Thus, statistics-based analysis is recommended to avoid the risk of over-interpretation. It is also possible that the likely morphometric signature of tectonically less active settings comprises spatially inconsistent information rather than it is typified by consistently low values of various morphometric parameters. •Applicability of morphometric indices in tectonic geomorphology re-assessed.•Critical steps in statistical analysis of morphometric indices are discussed.•Simple test proposed to evaluate the role of lithology versus tectonic forcing.•Inconsistent spatial distribution of index values may typify low-activity areas.